"The moral arithmetic": morality in the age of mathematics. Issue 2 (3rd April 2021) - Levy-Eichel, Mordechai
ABSTRACT: This article examines the influence of mathematics on early modern and modern moral thought. In particular, I trace the origin and development of the "moral arithmetic" (which has previously been misattributed); that is, the attempt to introduce quantificatory calculation to morality. Tracing the origins and development of both the term and the idea, I show that it was coined by the Third Earl of Shaftesbury in the seventeenth century, and that it contributed to the rise of rationalistic, utilitarian Benthamite thought in the nineteenth century, laying the foundations for the modern discipline of mathematical economics. In particular, I emphasize that, while today we habitually associate ideas of self-interest with "cold, hard" mathematical analyses, the original application of mathematics to moral thought began among the theologians and philosophers of the seventeenth and eighteenth centuries in order to combat ideas of self-interest. I conclude by reflecting on some of the problems with the scope and limits of the history of political thought, and argue for the importance of drawing intellectual history and the history of science, in particular the history of mathematics, closer together.